The Hague Convention on Protection of Children and Co-operation in Respect of Inter-country Adoption Seeking the Cultural Relativism of the Inter-country Adoption - Šklebená, Karolína; Zemanová, Štěpánka, 1975-; Trávníčková, Zuzana, 1977-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2013)
This thesis focuses on the rights of the child in respect to the inter-country adoption. It aims to seek the notions of cultural relativism within those fundamental rights which are immediately applicable on the process of adoption. The thesis bases its theoretical framework on the current discourse on the universality of human rights. The theory of the three levels of cultural relativism is applied on the Hague Convention on Protection of Children and Co-operation in Respect of Inter-country Adoption to demonstrate the cultural relativism of the Convention itself.
Vedoucí práce: Štěpánka Zemanová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses